2015
DOI: 10.1002/ece3.1832
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of the olive‐winged bulbul (Pycnonotus plumosus) in a tropical urban‐fragmented landscape

Abstract: With increasing urbanization, urban‐fragmented landscapes are becoming more and more prevalent worldwide. Such fragmentation may lead to small, isolated populations that face great threats from genetic factors that affect even avian species with high dispersal propensities. Yet few studies have investigated the population genetics of species living within urban‐fragmented landscapes in the Old World tropics, in spite of the high levels of deforestation and fragmentation within this region. We investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 65 publications
(81 reference statements)
1
8
0
Order By: Relevance
“…It had high hd and low π. Similar results have been reported for other bulbul species: olive-winged bulbul Pycnonotus plumosus (Tang et al 2016), light-vented bulbul P. sinensis (Song et al 2013), collared finchbill Spizixos semitorques (Gao et al 2011) and Philippines bulbul Hypsipetes philippinus (Silva-Iturriza et al 2010). High hd and low π reflect that the population has undergone rapid expansion from a small ancestral population, with a small effective population size (N e ) (Rogers & Harpending 1992).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It had high hd and low π. Similar results have been reported for other bulbul species: olive-winged bulbul Pycnonotus plumosus (Tang et al 2016), light-vented bulbul P. sinensis (Song et al 2013), collared finchbill Spizixos semitorques (Gao et al 2011) and Philippines bulbul Hypsipetes philippinus (Silva-Iturriza et al 2010). High hd and low π reflect that the population has undergone rapid expansion from a small ancestral population, with a small effective population size (N e ) (Rogers & Harpending 1992).…”
Section: Discussionsupporting
confidence: 81%
“…The time since expansion was estimated for YTB using the 1050 bp sequence of mtCR with a mutation rate of 1.6 to 2.8% per base pair per million years (Lerner et al 2011). Since life history parameters were not available for this species, we used a generation time of 1 yr based on the estimates for the olivewinged bulbul Pycnonotus plumosus (Tang et al 2016) and the Philippines bulbul Hypsipetes philippinus (Kennedy et al 2000).…”
Section: Historical Demographymentioning
confidence: 99%
“…This can be complemented with genetic studies to investigate the degree of gene flow between the subpopulations across Singapore (e.g. Tang et al 2016). Findings drawn from both field survey and genetic data can be incorporated into an endangered species management plan coordinated among various stakeholders as a follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we found that urban fragmentation can result in increased genetic drift and reduced gene flow for many organisms including both small (Gortat et al, ) and large mammals (Wilson, Farley, McDonough, Talbot, & Barboza, ), lizards (Delaney et al, ), amphibians (Hitchings & Beebee, ), fish (Mather, Hancox, & Riginos, ), insects (Keller, Nentwig, & Largiader, ) and plants (Hollingsworth & Dickson, ). Urban facilitation, however, resulted in reduced drift and increased gene flow in a variety of organisms including insects (Kamdem, Fouet, Gamez, & White, ; Vickruck & Richards, ), birds (Tang et al, ), mammals (Adams, van Heezik, Dickinson, & Robertson, ) and plants (Johnson, Prashad, Lavoignat, & Saini, ). Indeed, a wide variety of taxa also experienced no change in genetic drift and gene flow, including organisms as diverse as plants (Culley, Sbita, & Wick, ) and mammals (Atterby, Allnutt, MacNicoll, Jones, & Smith, ).…”
Section: Joint Effects Of Urbanization On Genetic Drift and Gene Flowmentioning
confidence: 99%
“…In contrast, isolation‐by‐resistance (IBR, McRae, ) models predict that in addition to geographic distance, other factors (e.g., roads and buildings) provide varying levels of resistance to gene flow, many of which act in nonlinear and nonadditive ways. Urban features may act as either complete barriers or conduits to gene flow, or may act somewhere along the continuum from barrier to conduit (Crispo et al, ; de Groot et al, ; Holderegger & Di Giulio, ; LaPoint, Balkenhol, Hale, Sadler, & van der Ree, ; Tang, Sadanandan, & Rheindt, ). Although there is great heterogeneity of anthropogenic landscape features found within and between cities, it is unclear the extent to which urban fragmentation and facilitation models have been applied to landscape genetic analyses.…”
Section: Introductionmentioning
confidence: 99%